TINGKAT PENGETAHUAN DAN PERILAKU MASYARAKAT TERKAIT PENGGUNAAN KOSMETIKA TABIR SURYA SERTA PREDIKSI TOKSISITAS BAHAN TABIR SURYA SECARA IN SILICO - Azhara Andavia, Savira
Indonesian used sunscreen as means of protection from ultraviolet rays which categorized as highly until very extremely hazardous for skin health. Product effectivity and compound safety are crucial information for consumers to acknowledge so that a sunscreen provides optimal benefits. This study aims to evaluate the knowledge as well as to study the behavior of the population of West Java toward sunscreen used and also to predict toxicity of sunscreen compound to find out the safety profile. Evaluation of knowledge and behavior was done through survey to a sample of Wast Java population followed by analysis using SPSS. As for the toxicity prediction, a test using in silico method was carried out towards 13 sunscreen compounds registered in BPOM regulation No.23/2019 regarding the Technical Requirements of Cosmetic Materials. Before the tests were carried out, the methods were verified using classification models and its significance value was determined by Cooper statistics. The verified methods are OECD QSAR Toolbox v.4.4.1, TEST v.5.1, Toxtree v.3.1.0, and VEGA Hub v.1.1.5. Based on questionnaire result, knowledge level of sample categorized as moderate with the score and behavior level still categorized as less correct. The toxicity prediction test showed that the sensitizing compounds are avobenzone, enzacamene, oxybenzone, sulisobenzone, octinoxate, amiloxate, octocrylene, and ensulizole. The carcinogenicity and genotoxicity test showed that compounds with corresponding property are meradimate and padimate o, while the non-genotoxic carcinogen compounds are padimate o and octisalate. Only one compound was shown to exhibit mutagenic property which was Meradimate. The sunscreen compounds displayed developmental toxicity trait in general, with the exclusion of padimate o, octinoxate, and amiloxate. The compounds predicted to exhibit corrosive trait toward skin are octisalate and homosalate, while the compound which may cause serious lesion in eye is sulisobenzone.